The effects of cold treatment on the pupal period, emergence rate, and number of Protaetia brevitarsis larvae spawned. Issue 6 (12th December 2018) - Jang, Heeseung; Choi, Moon Bo; Lee, Hyoki; Kim, Yeongbu; Kwon, Ohseok
Abstract: To develop a system for the mass production of Protaetia brevitarsis larvae (Pbl), this study analyzed the oviposition characteristics of third instar Pbl through successive rearing and cold treatments. In the first generation, females laid 50 eggs each on average, and spawned higher numbers of eggs for the first 5 days but then fewer after this. However, all of the 2 nd ‐generation females that were produced through the successive rearing of eggs from the 1 st generation did not spawn. When test insects (TI) were raised at 32°C, their mean ± SE pupal period and emergence rate were 28.4 ± 1.9 days and 87%, respectively. However, most individuals raised in cold treatments (5°C and − 5°C) without a pre‐cooling period did not survive. Individuals exposed to a pre‐cooling period, however, had a 7–10 days longer pupal period than those raised at 32°C, and their emergence rate (90%) was slightly higher. Different cold treatment temperatures (0°C, 3°C, or 5°C) and periods (30 or 60 days) were tested in further experiments. The experimental group kept for 30 days at 0°C and 3°C had the shortest pupal period of all, and emergence rates exceeded 90% in most groups. With respect to the number of eggs spawned by the second generation females after cold treatments, the experimental groups held in cold treatments at 5°C for 30 and 60 days were found to spawn the most eggs. Consequently, the experimental group kept at 5°C for 30 days was the most effective set of conditions tested during the entire breeding period.